PENGARUH POLA ASUH ORANG TUA OTORITER, DEMOKRATIS DAN PERMISIF TERHADAP PERILAKU KEAGAMAAN SISWA DI SDN 32 TANJUNG BAKAU KECAMATAN TELUK KERAMAT - Juniardi Juniardi; Purniadi Putra; Jaelani Jaelani (STKIP Melawi, 2021)
This study aims to; (1) describe and analyze the effect of authoritarian parenting on students' religious behavior at SDN 32 Tanjung Bakau, Teluk Keramat District, (2) describe and analyze how much influence democratic parenting has on religious behavior in Indonesia. SDN 32 Tanjung Bakau, Teluk Keramat District, (3) describes and analyzes how much influence democratic parenting has on religious behavior in SDN 32 Tanjung Bakau, Teluk Keramat District, (4) describes and analyzes how much influence authoritarian parenting is, democratic and permissive towards religious behavior in SDN 32 Tanjung Bakau, Teluk Keramat District. This research is a descriptive quantitative research with the type of causal associative research (cause-effect). In this study consisted of 4 variables, namely the first variable student religious behavior, authoritarian parenting, democratic parenting, and permissive parenting. The population with research subjects were students of grade V SDN 32 Tanjung Bakau, amounting to 30 people. Data collection using a questionnaire method. Test the validity of the instrument by using the product moment analysis technique, while the reliability test using the alpha coefficient. The data analysis technique used multiple regression analysis. Prior to data analysis, the normality test analysis requirements were first carried out. The results showed that: (1) there was an influence of authoritarian parenting on religious behavior, the magnitude of the influence was 0.004 (0.4%) (2) there was a positive and significant effect of parenting style of democratic parents on religious behavior of 0.614 (61.4 %), (3) there is an influence of permissive parenting styles on religious behavior, the magnitude of the influence is 0.026 (2.6%), (4) there is a positive and significant influence on parenting styles for authoritarian, democratic and permissive parents on religious behavior by contributing 0.629 (62.9%) means that the influence between the variables of authoritarian parenting (1), democratic parenting (X2) and permissive parenting (X3) on religious behavior (Y) means that it has high strength